2008
DOI: 10.1021/jp0773785
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Self-assembly in the Gas Phase:  Bis(2-ethylhexyl)sulfosuccinate-Alkaline Metal Ion Aggregates

Abstract: The coating effect of alkali metal salt clusters by the surfactant anion bis(2-ethylhexyl)sulfosuccinate has been investigated by electrospray ionization mass spectrometry (MS) and MS/MS. The analysis of the data emphasized the formation and stability in the gas phase of reverse micelle-like surfactant aggregates carrying in their interior ionic clusters. Two main contributions have been postulated to account for the observed stability: intra-aggregate electrostatic interactions and screening of inter-aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
52
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 22 publications
6
52
0
Order By: Relevance
“…In contrast with enormous work devoted to NaAOT aggregates in solution, only a handful of investigations have been reported concerning NaAOT aggregates as charged species in the gas phase [8][9][10][11][12][13][14][15][16], including electrospray ionization (ESI) and matrix-assisted laser desorption/ionization mass spectra [10,14], time-offlight secondary ion mass spectra [16] and infrared multiple photon dissociation spectra [13] of singly and doubly positively charged NaAOT aggregates. These measurements revealed reverse micelle-like structures for these aggregates.…”
mentioning
confidence: 99%
“…In contrast with enormous work devoted to NaAOT aggregates in solution, only a handful of investigations have been reported concerning NaAOT aggregates as charged species in the gas phase [8][9][10][11][12][13][14][15][16], including electrospray ionization (ESI) and matrix-assisted laser desorption/ionization mass spectra [10,14], time-offlight secondary ion mass spectra [16] and infrared multiple photon dissociation spectra [13] of singly and doubly positively charged NaAOT aggregates. These measurements revealed reverse micelle-like structures for these aggregates.…”
mentioning
confidence: 99%
“…Positively and negatively charged aggregates containing alkaline metal ions have been previously described by us . In the case of positively charged AOT‐alkaline metal ion aggregates, trimeric species [AOT 3 M 4 ] + show an extra stability with respect to the other aggregates . Tandem and energy resolved mass spectrometry have shown that positively charged AOT‐alkaline metal ion aggregates mainly decompose by the loss of neutral surfactant molecules .…”
Section: Introductionmentioning
confidence: 79%
“…Gas‐phase AOTNa self‐assembling and its ability to incorporate ionic species in its aggregates have been studied by electrospray (ESI), matrix assisted laser desorption ionizations and energy‐resolved mass spectrometry . Positively and negatively charged aggregates containing alkaline metal ions have been previously described by us . In the case of positively charged AOT‐alkaline metal ion aggregates, trimeric species [AOT 3 M 4 ] + show an extra stability with respect to the other aggregates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, self-assembly of polymers has been demonstrated as a powerful method to generate well-ordered structures of the metal particles with uniform nano-size [20][21][22][23] . The core-shell architecture of the micelles would protect the metal nanoparticles from aggregation and makes them distribute uniformly in the solution [24] .…”
Section: Introductionmentioning
confidence: 99%